Dispersion stability of graphene in bio-based lubricant and its effect on tribological properties / Muhammad Harith Hasnul - Muhammad Harith, Hasnul (2021)
The upsurge in the usage of petroleum-based product nowadays have caused huge alarming concern to the society as they are non-renewable and harmful to the environment. Therefore, it is important to hunt for a suitable alternative such as bio-based lubricant. However, bio-based lubricant cannot perform well on its own, hence there is need for suitable additives to be introduced. Graphene is a promising additive due to its unique two-dimensional structure and remarkable properties. However, several reports have stated that graphene is unable to form a stable suspension in the lubricant. Hence this study was carried out to study the dispersibility of graphene in bio-based lubricant and how it will affect to its tribological performance as well as choosing a suitable surfactant to counter this low dispersibility. To achieve this, three bio-based polyol esters i.e., neopentyl glycol dioleate (NPG), trimethylol propane trioleate (TMP) and pentaerythritol tetraoleate (PE) were selected as base oil for graphene to be dispersed in. The graphene nanoparticles were added at various concentration (0.01 wt.%, 0.03 wt.%, 0.05 wt.%, 0.07 wt.% and 0.10 wt.%) into the base oils via magnetic stirrer. Three surfactant (ionic liquid, oleic acid and Triton X-100) were used to improve the dispersion stability of graphene. The dispersion stability of graphene was observed using sedimentation method and UV-Vis spectroscopy for over one month. Tribological behaviour of base oil with graphene before and after one month were tested using fourball tribotester whereas samples with surfactant were tested using high frequency reciprocating rig (HFRR). Worn surface from HFRR testing were observed under scanning electron microscope, energy-dispersive X-ray spectroscopy. Raman spectroscopy and optical surface analyser. In term of physical properties, no significant change is observed after the addition of graphene and surfactant. Varying suspension stability were observed in different base oil which indicated there is a matter of compatibility when selecting the base oil for graphene additive. Based on the tribological tests, graphene is more promising as an antiwear additive compared to its performance as a friction modifier. After one month, graphene sedimentation reduced its tribological performance and the more stable suspension retained its performance. Out of all surfactant, ionic liquid is the most promising surfactant as stable suspension is observed for over one-month. Synergistic behaviour of graphene and ionic liquid have been confirmed as this combination significantly improved its tribological performance.